To solve this system of equations, we can use the method of elimination. First, we'll add the two equations together to eliminate the y variable:
(6x - 5y) + (3x + 5y) = 27 + 36
9x = 63
Now we can solve for x by dividing both sides of the equation by 9:
9x/9 = 63/9
x = 7
Now that we have the value of x, we can substitute it back into one of the original equations to solve for y. Let's use the first equation:
6(7) - 5y = 27
42 - 5y = 27
Next, we'll move the constant term to the other side of the equation:
-5y = 27 - 42
-5y = -15
Finally, we'll divide both sides of the equation by -5 to solve for y:
y = -15 / -5
y = 3
So the solution to the system of equations is x = 7 and y = 3.
Solve the system of equations.
6x–5y=27
3x+5y=36
1 answer